Normative Regulation for the Application of Specialized Knowledge in Civil Proceedings - O. G. D’yakonova (Теория и практика судебной экспертизы)
Based on the analysis of use of specialized knowledge in legal proceedings, the author reveales its common forms and types applied in civil and administrative proceedings. The problems and conflicts generated by the legal regulation of the use of specialized knowledge in legal proceedings have also been reviewed. As a result, the author concludes that there is no unified approach to the legal regulation of forensic expertise and the participation of a specialist in civil and administrative proceedings.Practically there arise some problems associated both with the appointment and production of a forensic examination, and with the participation of a specialist in procedural actions.The inability to resolve certain issues results in the recognition of evidence as inadmissible. One of the main reasons for this is the adoption of procedural codes and amendments and additions to them without considering the provisions developed by the science of forensic expertology. The author emphasizes that forensic expertology studies legal, including normative, theoretical, and methodological issues of the use of specialized knowledge in legal proceedings basing on the integrated approach, and so it does not monopolize the subject of research, but provides a versatile approach to it, considering the developments of procedural sciences. As a result, forensic expertology can act as the fundamental knowledge for normative regulation and implementation of legal institutions of forensic expertise and participation of a specialist.